2020
DOI: 10.1371/journal.pone.0227450
|View full text |Cite
|
Sign up to set email alerts
|

Murine Surf4 is essential for early embryonic development

Abstract: Newly synthesized proteins co-translationally inserted into the endoplasmic reticulum (ER) lumen may be recruited into anterograde transport vesicles by their association with specific cargo receptors. We recently identified a role for the cargo receptor SURF4 in facilitating the secretion of PCSK9 in cultured cells. To examine the function of SURF4 in vivo, we used CRISPR/Cas9-mediated gene editing to generate mice with germline loss-of-function mutations in Surf4. Heterozygous Surf4 +/mice exhibit grossly no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Indeed, Surf4 is essential for early development in animals. Its homozygous knockout caused embryonic lethality in both Caenorhabditis elegans and mice 26 , 48 , suggesting that Surf4 plays a broader role in protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Surf4 is essential for early development in animals. Its homozygous knockout caused embryonic lethality in both Caenorhabditis elegans and mice 26 , 48 , suggesting that Surf4 plays a broader role in protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in human cells have also implicated SURF4 in the trafficking of other cargoes, including apolipoprotein B (APOB) (Emmer et al, 2020;Saegusa et al, 2018;, erythropoietin (EPO) (Lin et al, 2020), growth hormone, dentin sialophosphoprotein, and amelogenin (Yin et al, 2018). A role for SURF4 in APOB secretion was further supported by a recent study in which acute deletion of hepatic Surf4 in adult mice caused hypocholesterolemia and a reduction in hepatic lipoprotein secretion (X.…”
Section: Introductionmentioning
confidence: 94%
“…23 Deficiency of Surf4 in mice results in embryonic lethality after implantation. 21 A study of lipoprotein transport revealed that SURF4-mediated ER export of lipoproteins controls lipid homeostasis in mice and humans. 24 During mouse preimplantation development, Surf4 was highly enriched in MII oocytes 9,25 and early embryos before the two-cell stage.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 15 , 16 , 17 , 18 , 19 Disruption of Surf4 trafficking results in a reduction in the number of ERGIC clusters 20 and accumulation of cargo proteins in the ER compartment. 21 Dysregulation of ER‐Golgi vesicle transport induces ER stress, 22 and in turn, when ER stress occurs, the expression of Erv29p significantly increases. 23 Deficiency of Surf4 in mice results in embryonic lethality after implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation